Systematic Review of the Influence of Intellectual Capital on Firm Value: A Study of Mining Companies Listed on the Indonesia Stock Exchange - Nadilla Vidya Putri; Iskandar Muda Damanik; Parapat Gultom (International Forum of Researchers and Lecturers, 2025)
This study systematically reviews the influence of intellectual capital (IC) on firm value among mining companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The mining industry, typically capital-intensive and asset-heavy, is undergoing transformation as intangible assets such as knowledge, innovation, and organizational capabilities become critical for sustaining competitive advantage. The central research problem concerns how and to what extent IC—measured through human capital efficiency (HCE), structural capital efficiency (SCE), and capital employed efficiency (CEE)—affects firm value, particularly as reflected in Tobin's Q. This paper aims to synthesize findings from recent empirical studies to determine whether IC contributes significantly to market-based valuation in the mining sector. Using a systematic review approach, the study selects peer-reviewed literature applying quantitative methods, especially panel data regression models employing the VAIC™ framework. The results consistently indicate that IC positively impacts firm value, with HCE and CEE emerging as dominant drivers, while SCE shows varied effects. The findings support the Resource-Based View (RBV) theory, suggesting that IC components represent unique, valuable, and hard-to-imitate resources. The synthesis highlights that although mining firms are still adapting to intangible value drivers, those investing in human capital and capital efficiency enjoy higher valuations. The paper concludes that intellectual capital should be an integral part of strategic management in mining firms to sustain growth and investor confidence. Future research should include cross-sectoral and longitudinal analyses for broader generalizability.